The impact of bimodal pore size distribution and wettability on relative permeability and capillary pressure in a microporous limestone with uncertainty quantification. (January 2023) - Zhang, Guanglei; Foroughi, Sajjad; Raeini, Ali Q.; Blunt, Martin J.; Bijeljic, Branko
Highlights: We provided new multiphase flow measurements in a carbonate limestone with complex geometry and wettability. We discussed its unique features related to contact angle, pore occupancy, curvature, capillary pressure and relative permeability. The relative permeability values were corrected by considering the measured saturation profile along the sample length to correct for the so-called capillary end effect. Greyscale based differential imaging was used and demonstrated for accurately determining the porosity and saturation without segmentation. We demonstrated that not only wettability but also pore size distribution and microporosity have significant impact on displacement processes. Abstract: Pore-scale X-ray imaging combined with a steady-state flow experiment was used to study the displacement processes during waterflooding in an altered-wettability carbonate, Ketton limestone, with more than two orders of magnitude difference in pore size between macropores and microporosity. We simultaneously characterized macroscopic and local multiphase flow parameters, including relative permeability, capillary pressure, wettability, and fluid occupancy in pores and throats. An accurate method was applied for porosity and fluid saturation measurements using greyscale based differential imaging without image segmentation. The relative permeability values were corrected by considering the measured saturation profile along the sample length to account for the so-called capillary end effect. The behaviour of relative permeability and capillary pressure was compared to other measurements in the literature to demonstrate the combined effects of wettability and pore structure. Typical oil-wet behaviour in resolvable macropores was measured from contact angle, fluid occupancy and curvature. The capillary pressure was negative while the oil relative permeability dropped quickly as oil was drained to low saturation and flowed through connected oil layers. Brine initially largely flowed through water-wet microporosity, and then filled the centre of large oil-wet pore bodies. Thus, the brine relative permeability remained exceptionally low until brine formed a connected flow path in the macropores leading to a substantial increase in relative permeability. Overall, this work demonstrates that not only wettability but also pore size distribution and microporosity have significant impact on displacement processes.